(untitled) (Global Journal of Science Frontier Research, 2022)
This review presents the results of studies on the issue of reducing the amount of heterocyclic aromatic amines formed in meat products. The analyzed works have shown that it is possible to influence the amount of heterocyclic aromatic amines through their precursors, heat treatment of meat products, and the introduction of non-meat ingredients into the recipe. An analysis of works devoted to the effect of temperature and duration of heat treatment on the amount of heterocyclic aromatic amines formed is presented. As a result of the analysis, it was found that free amino acids, moisture, and the water-holding capacity of the raw material play an essetial role in the formation of heterocyclic aromatic amines. Many analyzed works proved the inhibitory effect of vitamin E in the formation of heterocyclic aromatic amines. Inhibitory effects of pomegranate seed extract, artichoke extract are described. The impact of replacing animal fat with vegetable oils on the amount of heterocyclic aromatic amines formed is described.